Militias in Civil Wars - Jentzsch, C; Kalyvas, SN; Schubiger, LI (SAGE Publications, 2015)
Militias are an empirical phenomenon that has been overlooked by current research on civil war. Yet, it is a phenomenon that is crucial for understanding political violence, civil war, post-conflict politics, and authoritarianism. Militias or paramilitaries are armed groups that operate alongside regular security forces or work independently of the state to shield the local population from insurgents. We review existing uses of the term, explore the range of empirical manifestations of militias, and highlight recent findings, including those supplied by the articles in this special issue. We focus on areas where the recognition of the importance of militias challenges and complements current theories of civil war. We conclude by introducing a research agenda advocating the integrated study of militias and rebel groups.